Covid 19: change of perception towards food habit and assessing a new opportunity for Indigenous farmers - Vinuchakravarthi, V; Srinivasan , S (Journal of Postharvest Technology, 2024)
The study aims at understanding changing nature of food habit as Covid pandemic is new to this generation which they never experienced  earlier. People started to realize the importance of good food in building good immune system. Many People started to believe in native  medicines, remedies etc. And started to give priority in adding fresh traditional/ native foods in their food menu and this paper is an attempt to  understand the changes in food habit and mainly acceptability to buy farm fresh native foods direct from the farmers which is an opportunity  for the farmers to improve their earnings. This study has thrown some light in peoples acceptability for native foods and also there is a  positive change in the prioritizing traditional foods and also their willingness to purchase farm fresh produce.
Keywords: Covid 19; organic farming; indigenous farming; agri marketing; direct marketing